Effect of Cardiac Rehabilitation Program on Heart Rate Recovery after Percutaneous Coronary Intervention and Coronary Artery Bypass Grafting - Abbas Soleimani; Mohammad Alidoosti; Mojtaba Salarifar; Seyed Ebrahim Kassaian; Abbasali Karimi; Saeed Davoodi; Mehrab Marzban; Seyed Hesameddin Abbasi; Mostafa Nejatian; Ali Abbasi (Journal of Tehran University Heart Center, 2008)
Background: The objective of this study was to evaluate the effect of a hospital-based cardiac rehabilitation program on heart rate recovery (HRR) in patients who received percutaneous coronary intervention (PCI) or coronary artery bypass grafting (CABG).